Django 2.2 and Python the ultimate web development bootcamp - Walter, Nick (Packt Publishing, 2019)
"In this Django course, you'll be guided through the Django web framework from start to end. If you're going to be working with Python, especially for web applications or web design, learning the Django framework will be useful and this course will help you do just that. Throughout this course, you'll be presented with coding quizzes and challenges to test everything you learn. This format will allow you to learn Django effectively. Although you will use Python in this course, you do not need prior experience in the language as the course offers an introduction to Python to get you up-to-speed. As you progress, you'll also explore Git, which is a useful tool that allows you to create multiple versions of your code. In addition to this, the course will demonstrate how to take the projects that you make in this course and publish them live on the web through a Virtual Private Server. By the end of this course, you will have developed the skills you need to create exciting web applications using Django 2.2"--Resource description page
Title from resource description page (Safari, viewed February 17, 2020)
Keywords: Django (Electronic resource); Web site development; Application software -- Development; Python (Computer program language); Application program interfaces (Computer software); Sites Web; Développement; Logiciels d'application; Développement; Python (Langage de programmation); Interfaces de programmation d'applications; APIs (interfaces); Application software; Development; Instructional films; Films de formation